2021
DOI: 10.3390/brainsci11081051
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the COVID19-Related Lockdown Are Modulated by Age: An Italian Study in Toddlers and Pre-Schoolers

Abstract: Although the issue has been repeatedly explored, data on the impact of the COVID-19 pandemic on children’s sleep quality are inconsistent. To clarify these discrepancies, here we investigate possible age-related differences. During the lockdown, 112 parents of toddlers (0–3 years, N = 61) and pre-schoolers (4–5 years, n = 51) completed an online survey including the Children’s Sleep Habits Questionnaire (CSHQ). Sleep-related items required an additional retrospective judgment, referring to the pre-pandemic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 54 publications
(118 reference statements)
1
16
0
Order By: Relevance
“…The preliminary studies that took place in Italy identified a weak impact [ 1 ], and then in following participants during four weeks, suggested they are transient [ 2 ]. Subsequent studies that took place in a mix of countries generally corroborate the observation of a delayed sleep phase, but are conflictual with regard to a negative sleep impact [ 1 , 3 , 4 , 5 , 6 ]. For example, Liu et al [ 5 ] in China found a reduction in sleep disorders in 4–6 year-olds, and Cerasuolo et al [ 6 ] in Italy found an improvement in overall sleep quality also in this age group, but not for children 0–3 years old (in whom sleep was stable).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…The preliminary studies that took place in Italy identified a weak impact [ 1 ], and then in following participants during four weeks, suggested they are transient [ 2 ]. Subsequent studies that took place in a mix of countries generally corroborate the observation of a delayed sleep phase, but are conflictual with regard to a negative sleep impact [ 1 , 3 , 4 , 5 , 6 ]. For example, Liu et al [ 5 ] in China found a reduction in sleep disorders in 4–6 year-olds, and Cerasuolo et al [ 6 ] in Italy found an improvement in overall sleep quality also in this age group, but not for children 0–3 years old (in whom sleep was stable).…”
Section: Introductionmentioning
confidence: 91%
“…Subsequent studies that took place in a mix of countries generally corroborate the observation of a delayed sleep phase, but are conflictual with regard to a negative sleep impact [ 1 , 3 , 4 , 5 , 6 ]. For example, Liu et al [ 5 ] in China found a reduction in sleep disorders in 4–6 year-olds, and Cerasuolo et al [ 6 ] in Italy found an improvement in overall sleep quality also in this age group, but not for children 0–3 years old (in whom sleep was stable). In contrast, Lecuelle et al [ 7 ] in France found a 22% increase in sleep disorders in the young child age group, and Bruni et al [ 8 ] in Italy also found disturbances in young children for sleep variables (e.g., in duration, falling asleep, night awakenings, and parasomnias).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations